Grandparenting and well-being of the elderly in China - Hao Wang; Jan Fidrmuc; Qi Luo (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Grandparenting duties can affect the well-being of the elderly both positively and negatively. This paper disentangles the interactions between grandparenting, quality of life, and life satisfaction in China. Using a panel dataset of 3,205 respondents in three waves of the China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013, and 2015, we find that grandparents who look after grandchildren are less at risk of depression, receive more financial and in-kind transfers from their children, and report greater life satisfaction than grandparents who do not look after grandchildren. These benefits vary across gender and rural-urban status, however. The positive effect of grandparenting is driven mainly by the direct effect with negligible mediating effect attributable to better quality of life.
URN:NBN:fi:bof-202008122273
Keywords: D13; O18; 330; grandparenting; quality of life; life satisfaction; panel data analysis; CHARLS